Knowledge, attitudes, and practices regarding malaria control among the slash and burn cultivators in Rangamati Hill tracts of Bangladesh - Saha, Avijit; Sarker, Malabika; Kabir, Moktadir; Lu, Guangyu; Müller, Olaf (BMC, 2022)
This article was published in the BMC Malaria Journal [© The Author(s) 2019. This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/)] and the definite version is available at: https://doi.org/10.1186/s12936-019-2849-0 The Journal's website is at: https://malariajournal.biomedcentral.com/articles/10.1186/s12936-019-2849-0#citeas